Instrumentation Time of Rotary Files and Manual Files in Pulpectomy of Primary Molars: A Systematic Review - M. Elamathe; Sharath Asokan; P.R. Geethapriya; V. Vijayasankari (International Journal of Pharma and Bio Sciences, 2021)
Rotary armamentarium used in the endodontic treatment of primary teeth has become a boon for pediatric dentists. However, the effectiveness of the rotary files in reduction of instrumentation time over manual files has not been systematically evidenced. This systematic review attempted to assess the difference in the instrumentation time between the rotary and manual files used for pulpectomy in the primary molars. Literature search through electronic databases for relevant articles published from January 2000 to April 2020 was done using the keywords. Grey literature search and hand search of the reference list of the selected articles were also carried out. All the articles included in this review were subjected to quality assessment using the Cochrane Risk of Bias 2 (RoB2) tool. 6800 articles were filtered from the database search and hand search. 40 Repeated articles were excluded. After applying the limits, 476 articles were obtained. Four hundred and fifty-four articles were excluded after reading the title and abstract. After assessing the full text, 14 articles were finally included for the review. Among the 14 articles, 13 articles reported that the instrumentation time of rotary files was significantly lesser when compared to the manual files. The same rotary file system showed different instrumentation time in different studies because of failure in standardizing the start and endpoint of instrumentation time. Studies which used sequential rotary files had higher instrumentation time than the studies using a single file rotary system. Operator’s experience, child’s compliance and tooth selected for the study also played a major role in instrumentation time. The risk of bias assessment revealed that only one article fell under low-risk category, eight articles fell under some concerns category and five articles were graded as high-risk category. Rotary files present a favourable reduction of instrumentation time compared to manual files, but there is a paucity of high-quality research with a standard method to record the instrumentation time.